معاشی وتجارتی مسائل پر مجمع الفقہ الاسلامی جدہ کی قرارات کا جائزہ: A Review of the Decisions of Majmaʻ al-Fiqh al-Islāmī on Economic and Commercial Issues (Al-Qamar, 2021)
Islam provides way to its followers in all   aspects and activities of life, in economic values, social values as well as ethical values. Its basic   guidance about the economics is mentioned in various   verses of the Quran. Everyone knows that human livelihood is in constant progress, therefore, many problems of economics are arising day by day. The scholars continued to give fatwa in the light of the qur 'an   and hadith in order to solve the problems of these economic   issues. In this article, international Fiqh Academy Jeddah’s   resolutions have been described in which daily economic problems have been resolved like zakat on depts, insurance and reinsurance, inflation and the Changing Value of Currency etc.
Keywords: Majmaʻ al-Fiqh al-Islāmī; Economic and Commercial Issues; Decisions; Review